Generative AI and ChatGPT : quickstart with examples. (Packt Publishing, 2023)
This course delves deep into the OpenAI API, gaining expertise in NLP and code generation. Learn to leverage the Completions endpoint, optimize prompt design, and understand token usage. With hands-on projects such as fact-based search, image generation, and code completion, we will acquire practical skills and use Node.js, React.js, and Next.js to build cutting-edge applications. This comprehensive course begins with an introduction to the OpenAI API and a deep understanding of its NL and code processing capabilities. We will explore the Completions endpoint and tackle various NLP tasks such as content generation, summarization, semantic search, and sentiment analysis. We will discover the different models available, including the cutting-edge GPT-3 model, and learn to apply them to solve unique use cases. We will master the art of prompt design and settings to optimize API output and control generated text. We will acquire a comprehensive understanding of tokens and their role in controlling API response. We will engage in hands-on projects, build apps like a fact-based search, and generate images using DALL-E. With a focus on cutting-edge tech stacks such as Node JS, ReactJS, and NextJS, you will be equipped to build advanced apps. Upon completion, you will have the skills to leverage OpenAI API and revolutionize NLP and code generation abilities. What You Will Learn Interact and perform various natural language (NLP) tasks with GPT-3 Translate natural language to code, perform code continuation Experiment with code examples, OpenAI playground, and API models Generate new images from scratch with the DALL-E model Apply text completion and various other language-processing tasks Build a simple application with the text completion endpoint Audience The course is suitable for JavaScript developers, both front/backend, who want to enhance their skills in web development. It also benefits students studying web development and software engineering, as it covers essential concepts and techniques. The course is open to anyone interested in building apps with the OpenAI API and GPT-3 model. Prerequisites include basic HTML and CSS knowledge for web development, a solid understanding of JavaScript fundamentals, Visual Studio Code for coding, the latest version of Node.js, and a modern web browser with React Developer Tools extension is needed. About The Author Sandy Ludosky: Sandra L. Sorel is a freelance web and mobile developer based in Toronto, Ontario, Canada. With a specialization in front-end development, she is proficient in HTML, CSS, CSS3 animation, Sass, JavaScript, and jQuery. Sandra is passionate about creating beautiful and user-friendly websites using tools such as Adobe Creative Suite, including Photoshop, Illustrator, and Flash. She is also interested in web marketing, web analytics, visual design, video editing, photography, and WordPress development. As an avid learner, Sandra actively explores new technologies and digital advancements. Alongside her freelance work, she shares her knowledge and expertise as an instructor on Udemy, where she has received positive reviews and taught various courses.